Turbulent flow simulations around the front wing of a racing car - Liang, Chen (Cranfield University, 2010)
Aerodynamics has played a more and more important role in motorsports for maximising the race car performance. Amongst all the aerodynamic devices of race car, the front wing plays a vital role. In order to evaluate aerodynamic forces and develop new solutions for the race car, Computational Fluid Dynamics (CFD) has become a powerful tool. The most classical numerical simulations are based on solving the Reynolds Averaged Navier-Stokes (RANS) equations. In this project, the aerodynamics of front wings in ground effect has been studied using computational methods. A serious of simulations has carried out both for a single element wing and a double element wing by using DLR‟s FLOWer code. Simulations using three numerical schemes and three different turbulence models are carried out and the computational results were compared with the experimental data around the single element wing in ground effect. Further on, numerical studies on the aerodynamics performance have carried out for both single and double element wings in ground effect. For the investigation of different numerical methods and different turbulence models, the results obtained by using HLLC Riemann solver with 3rd order WENO schemes in conjunction with two-equation SST k-ω turbulence model shows more accurate simulations for the lift, drag coefficients and the pressure distributions at all heights. Furthermore, the numerical study on single element wing shows that the decreased height (to a certain level) and the increased angle of attack (up to the stall angle) will result in larger downforce. For the double element wing, various simulations were carried out under the configurations that the main element is fixed while the flap angle changes. The general tendency for both the downforce and the drag are similar with the single element wing, however the magnitude is much bigger. It is also found that the increased camber which made by the adding flap does not bring a significant vortex shedding after the trailing edge.